Legal Responsibilities of Notaries in the Era of Artificial Intelligence in Preventing Fraudulent Property Transactions - Lany, Arman (Jurnal Pembaharuan Hukum, 2025)
The development of Artificial Intelligence (AI) technology has had a significant impact on various sectors, including notarial services, particularly in preventing fraud in property transactions. However, the emergence of this technology raises questions about the changing paradigm of notaries' legal responsibilities as public officials. This study aims to analyze the impact of AI implementation on the role and legal responsibilities of notaries, identify regulatory challenges, and formulate policy recommendations to maintain legal protection and the integrity of the notarial system in the digital era. The research approach is normative, using secondary literature analysis in the form of laws and regulations, court decisions, and other relevant literature. Qualitative methods using prescriptive, comparative, and evaluative approaches were used to examine legal norms and their application. The findings indicate that while AI supports efficiency and fraud detection, legal interpretation and responsibility remain with notaries. Regulations need to be revised to ensure the use of AI is strictly and ethically regulated. The integration of AI does not diminish the responsibilities of notaries, and regulatory updates and increased human resource capacity are needed to address technological challenges while maintaining legal certainty and justice.